Advanced temperature sensing with Er3+/Yb3+ co-doped Ba2GdV3O11 phosphors through upconversion luminescence - Kachou, Ikhlas; Saidi, Kamel; Ekim, Utku; Dammak, Mohamed; Ersundu, Miray Celikbilek; Ersundu, Ali Ercin (ROYAL SOC CHEMISTRY, 2024)
Optical thermometry is a non-contact temperature sensing technique with widespread applications. It offers precise measurements without physical contact, making it ideal for situations where contact-based methods are impractical. However, improving the accuracy of optical thermometry remains an ongoing challenge. Herein, enhancing the thermometric properties of luminescent thermometers through novel materials or strategies is crucial for developing more precise sensors. Hence, the present study focuses on the application of four-mode luminescence thermometric techniques in sol-gel synthesized Er3+/Yb3+ co-doped Ba2GdV3O11 phosphors for optical temperature sensing in the temperature range of 298-573 K. The upconversion (UC) luminescence is achieved under excitations of 980 nm or 1550 nm, resulting in bright yellow-green emission in the visible spectral range. Temperature sensing is realized by exploiting the UC emissions of S-4(3/2), H-2(11/2) and F-4(7/2) bands, which represent intensity ratios of thermally coupled levels (TCELs) and non-thermally coupled levels (NTCELs) of Er3+/Yb3+, along with the emission lifetimes at S-4(3/2). The relative sensitivity (S-r) values for TCELs exhibit a gradual decrease with rising temperature, reaching a maximum of 1.1% K-1 for 980 nm excitation and 0.86% K-1 for 1550 nm excitation at 298 K. Conversely, for NTCELs, the highest S-r value observed is 0.9% K-1 at 298 K for 1550 nm excitation. Moreover, the emission lifetimes at S-4(3/2) yield notably high S-r values of up to 5.0% mu s K-1 (at 425 K). Furthermore, the studied phosphors have a sub-degree thermal resolution, making them excellent materials for accurate temperature sensing. Overall, this study provides a promising new direction for the development of more precise and reliable optical thermometry techniques, which could have important implications for a range of scientific and industrial optical temperature sensing applications.
Keywords: OPTICAL THERMOMETRY; NANOPARTICLES; NM; NANOCRYSTALS; EMISSION; ER3+; EU3+; EXCITATION; BEHAVIOR; LN(3+); Chemistry